Concentration od omega-3 PUFA extracted from yellow fin tuna (Thunnus albaceres) eyeballs by Lipase-catalyzed alcoholysis. - Braceros, Ma. Cecilia Esperanza Salgado (2000.)
Fish oil extracted from the eyeballs of yellowfin tuna (Thunnus albacares) by the aqueous method of lipid extraction as modifies by Panggat (1997)
Thesis (Undergraduate, Bachelor of Science in Fisheries) College of Fisheries, University of the Philippines in the Visayas, Miagao, Iloilo. 2000.
Keywords: Yellowfin tuna; Omega-3.